PERAN KOMITE SEKOLAH DALAM IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH - EKAWATI, HERLINA; HARYATI, TITIK; WURYANDINI, ENDANG (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to evaluate the role of the school committee in the implementation of School-Based Management (SBM) at SMA Negeri 1 Jepon. SBM provides autonomy to schools to manage resources and make decisions independently by involving various stakeholders. However, the observation results indicate that the role of the school committee at SMA Negeri 1 Jepon is still not optimal and tends to be symbolic, limited to administrative activities without significant contributions in planning, supervision, or educational resource mobilization. This research uses a descriptive qualitative approach with observation, interviews, and document studies as data collection techniques. The research results indicate that the lack of understanding among committee members and the minimal involvement of the school are the main factors hindering the strategic role of the committee. This study suggests empowering the committee through training and enhanced collaboration so that it can function as a strategic partner in supporting the improvement of education quality. The research findings are expected to serve as practical recommendations for optimizing the role of school committees in the implementation of School-Based Management (SBM). ABSTRAKPenelitian ini bertujuan untuk mengevaluasi peran komite sekolah dalam implementasi Manajemen Berbasis Sekolah (MBS) di SMA Negeri 1 Jepon. MBS memberikan otonomi kepada sekolah untuk mengelola sumber daya dan pengambilan keputusan secara mandiri dengan melibatkan berbagai pemangku kepentingan. Namun, hasil observasi menunjukkan bahwa peran komite sekolah di SMA Negeri 1 Jepon masih belum optimal dan cenderung simbolis, terbatas pada kegiatan administratif tanpa kontribusi signifikan dalam perencanaan, pengawasan, atau penggalangan sumber daya pendidikan. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan observasi, wawancara, dan kajian dokumen sebagai teknik pengumpulan data. Hasil penelitian menunjukkan bahwa kurangnya pemahaman anggota komite dan minimnya keterlibatan sekolah menjadi faktor utama yang menghambat peran strategis komite. Studi ini menyarankan pemberdayaan komite melalui pelatihan dan peningkatan kolaborasi agar dapat berfungsi sebagai mitra strategis dalam mendukung peningkatan mutu pendidikan. Hasil penelitian diharapkan menjadi rekomendasi praktis untuk optimalisasi peran komite sekolah dalam pelaksanaan MBS.